Comparative Hepatorenal Effects of Ethanolic Extracts of Vernonia amygdalina and Ocimum gratissimum in Streptozotocin-Induced Diabetic Wistar Rats - C. G. Ehie; A. S. Ezekwe; A. K. Okari; D. S. Lawson; U. P. Okpu (Health Science Research International, 2026)
Background: Diabetes mellitus is accompanied by biochemical and structural disturbances that may extend to the liver and kidneys. Vernonia amygdalina (bitter leaf) and Ocimum gratissimum (scent leaf) are widely used African medicinal plants with reported antioxidant and metabolic activities. Objective: This article evaluated the hepatorenal effects of ethanolic leaf extracts of V. amygdalina and O. gratissimum, administered individually and in combination, in streptozotocin (STZ)-induced diabetic Wistar rats. Methods: The study used 72 Wistar rats. Diabetes was induced with 65 mg/kg STZ following two weeks of high-fat feeding. Animals were assigned to normal control, diabetic untreated, metformin-treated, V. amygdalina-treated, O. gratissimum-treated, and combined-extract groups. Ethanolic extracts were prepared by Soxhlet extraction and administered orally for 28 days. Hepatic indices included alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin and total protein; renal indices included urea, creatinine, potassium, sodium and bicarbonate. Results: Relative to the untreated diabetic group, individual extracts produced generally lower hepatic and renal biochemical indices, with O. gratissimum showing the more favourable numerical pattern. ALP, ALT, AST and total bilirubin were 66.50 ± 1.40 U/L, 18.97 ± 0.23 U/L, 70.00 ± 0.91 U/L and 0.21 ± 0.01 mg/dL, respectively, in the O. gratissimum group, compared with 83.50 ± 1.27 U/L, 28.77 ± 0.20 U/L, 81.70 ± 1.30 U/L and 0.28 ± 0.01 mg/dL in untreated diabetic rats. Similarly, creatinine decreased from 0.41 ± 0.02 mg/dL in the diabetic control to 0.33 ± 0.01 mg/dL with O. gratissimum. In contrast, the combined extract produced the highest ALP, ALT, AST, bilirubin, urea, creatinine and electrolyte values and was accompanied by hepatic and renal structural abnormalities. Conclusion: Under the experimental conditions, the individual ethanolic extracts, particularly O. gratissimum, were associated with improved hepatorenal biochemical indices, whereas combined administration was associated with marked hepatic.